Acute Hemifacial And Hemiparesis Caused By Hemorrhagic Vestibular Schwannoma; A Case Report - Hatam, Jaber; Mokhtari, Mahisa; Ahmadi, Sayedali; Bahrami, Eshagh; Mirsalehi, Marjan; Mohebbi, Saleh; Abolmaali, Meysam (International Clinical Neuroscience Journal, 2022)
Vestibular schwannoma is a benign and common slow-growing tumor that develops on the vestibular divisions of cranial nerve VIII. Some risk factors may enhance intratumoral hemorrhage risk which leads to tumor management to early surgical procedures. Hence, we describe a 57-year-old man presented with hearing loss and a 5*8 mm vestibular schwannoma. Eight months later, the patient was referred with headache, nausea and vomiting, right hemifacial paresis, and hemiparesis. Magnetic resonance imaging (MRI) revealed a 45*35 mm hemorrhagic vestibular schwannoma. Surgical pathology reported hemorrhagic vestibular schwannoma. This was a rare case of hemorrhagic vestibular schwannoma with none of the established risk factors for the intratumoral hemorrhage and presented with Wallenberg-like syndrome. Many risk factors can cause hemorrhagic vestibular schwannoma. We present one case of small vestibular schwannoma without any predisposing of hemorrhage and acute onset of same side hemifacial paresis and hemiparesis.